The modern approaches to studying of influence of heavy metals as environment factor on growth of malignant - Мukasheva, М.А.; Аitkulov, А.М.; Makisheva, S. (Изд-во КарГУ, 2013)
In this article the main feature of action on people of carcinogenic agents is considered. This agents consist in large number of sources of their entry in environment and an organism of people, and complex combination of various factors. It creates certain difficulties on the track of a solution to the problem. The heavy metals is played a significant part of environmental pollution. The understanding of processes of migration and transition of elements from one environment in another has great practical value for studying of mechanisms and ways of impact on a human body and estimation of level of toxicity of chemical elements.
Keywords: chemical elements; transformation; heavy metals; multiple-factor influence; migratory properties; adaptation; mutagen effect; carcinogenic properties